2020
DOI: 10.1590/2177-6709.25.3.065-072.oar
|View full text |Cite
|
Sign up to set email alerts
|

Complications encountered during Forsus Fatigue Resistant Device therapy

Abstract: Introduction: Fixed functional appliances are non-compliant solutions to Class II malocclusion treatment. The clinician, however, should be careful of unexpected complications during the therapy. Methods: 58 female adolescents who presented with Class II malocclusion due to deficient mandible were treated with Forsus Fatigue Resistant Device (FFRD) therapy until an overcorrection to an edge to edge incisor relationship was achieved. Results: Incisor relationship and overjet were corrected successfully in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The most commonly encountered issues were breakage of bands or splints, breakage of telescoping mechanisms, loosening of bands or splints, trauma to buccal mucosa, rotated and/or intruded teeth, canting in the occlusal plane, and development of posterior cross bite. 4, 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly encountered issues were breakage of bands or splints, breakage of telescoping mechanisms, loosening of bands or splints, trauma to buccal mucosa, rotated and/or intruded teeth, canting in the occlusal plane, and development of posterior cross bite. 4, 5…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly encountered issues were breakage of bands or splints, breakage of telescoping mechanisms, loosening of bands or splints, trauma to buccal mucosa, rotated and/or intruded teeth, canting in the occlusal plane, and development of posterior cross bite. 4,5 This versatile appliance almost takes care of all the disadvantages encountered with routine FFA. As the upper and lower posterior teeth are all engaged to a rigid rectangular archwire there is no eruption of posteriors which causes and increase in lower anterior facial height.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used a different survey to assess overall impression of the appliance and advised clinicians to be vigilant about cheek irritations. Recently, Elkordy et al 35 demonstrated the clinical complications faced during the FFRD therapy and encountered complications of FFRD as breakage, separation of parts, spring fatigue, sheared molar tubes, soft tissue swelling, and severe cheek irritation. Subsequently, the authors advised to inform patients before the start of the FFRD therapy.…”
Section: Discussionmentioning
confidence: 99%